Microneedling Combined with Platelet-Rich Plasma for Melasma: A Systematic Review and Meta-Analysis - Devy Maryam; Ida Ayu Diah Purnama Sari; Aditya Prabawa (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2026)
Background: Melasma is a chronic acquired hyperpigmentation disorder that can cause significant psychosocial impact despite being asymptomatic. Conventional management often provides limited or temporary results. The combination of microneedling and platelet-rich plasma (PRP) has gained increasing attention due to their complementary roles in promoting skin regeneration and improving treatment efficacy. Purpose: This systematic review and meta-analysis aimed to synthesize data from randomized controlled trials and clinical studies published within the last decade to explore the therapeutic benefits and potential of microneedling combined with PRP in melasma management. Methods: A comprehensive search was conducted across PubMed, the Cochrane Library, Wiley Online Library, and supplementary sources, up to August 2025. Eligible studies included randomized and non-randomized clinical trials assessing microneedling followed by topical PRP. Data were pooled using random-effects (SMDs), and heterogeneity was assessed using the I2 statistic. Risk of bias was evaluated using Cochrane RoB 2.0 and ROBINS-I tools.  Result: Seven studies involving 189 participants were included. Pooled analyses demonstrated significant reductions in MASI and related indices favoring microneedling with PRP. Effect sizes increased across follow-up points (baseline to final: SMD = –1.71; 95% CI = –2.64 to –0.81; p = 0.002), despite moderate-to-high heterogeneity. Conclusion: The combination of microneedling and PRP appears to offer promising clinical benefits for the management of melasma. However, due to limited study numbers, high heterogeneity, and short follow-up durations, the findings should be interpreted with caution. Further large-scale, multicenter randomized trials are warranted to confirm its long-term efficacy and establish standardized treatment protocols.